東南極リュツォ・ホルム湾におけるインフラサウンド観測網の現状 - 村山, 貴彦; 金尾, 政紀; 山本, 真行; 石原, 吉明; 松島, 健; 柿並, 義宏; Takahiko Murayama; Kanao, Masaki; Yamamoto, Masa-yuki; Ishihara, Yoshiaki; Matsushima, Takeshi; Kakinami, Yoshihiro (2014)
conference object